2003
DOI: 10.1364/josaa.20.000903
|View full text |Cite
|
Sign up to set email alerts
|

Inverse problem in optical diffusion tomography IV Nonlinear inversion formulas

Abstract: We continue our study of the inverse scattering problem for diffuse light. In contrast to our earlier work, in which we considered the linear inverse problem, we now consider the nonlinear problem. We obtain a solution to this problem in the form of a functional series expansion. The first term in this expansion is the pseudoinverse of the linearized forward-scattering operator and leads to the linear inversion formulas that we have reported previously. The higher-order terms represent nonlinear corrections to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 16 publications
5
63
0
Order By: Relevance
“…A discussion on the range of validity of the weak scattering solution is given in Appendix B. Note that an exact representation of the higher order terms that extends the range of validity of such weak scattering approximations can be obtained by expanding V s n into a series of higher order perturbed contributions within the perturbation theory framework as was carried out for continuous media in [22][23][24] or, alternatively, as in [25].…”
Section: The Scattered Voltage Wavementioning
confidence: 99%
“…A discussion on the range of validity of the weak scattering solution is given in Appendix B. Note that an exact representation of the higher order terms that extends the range of validity of such weak scattering approximations can be obtained by expanding V s n into a series of higher order perturbed contributions within the perturbation theory framework as was carried out for continuous media in [22][23][24] or, alternatively, as in [25].…”
Section: The Scattered Voltage Wavementioning
confidence: 99%
“…where φ = u i − u. Physically, the scattering data φ(x 1 , x 2 ) is proportional to the change in intensity measured by a point detector at x 2 ∈ ∂Ω due to a point source at x 1 ∈ ∂Ω [3]. Each term in the series is multilinear in η and the operator K j is defined by…”
Section: Forward Problemmentioning
confidence: 99%
“…Such an approach gives rise to image reconstruction algorithms that, at present, are not well understood mathematically. In previous work, we have shown that, to some extent, it is possible to fill this gap by employing methods which invert the Born series [3]. The resulting image reconstruction algorithms are fast, direct, and have analyzable convergence, stability and approximation error [4].…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Though the algebraic structure of series solutions to different ISPs is similar, their analytic structure and convergence properties are quite different. This is a reflection of the underlying physical difference between the shortrange propagation of evanescent waves in NFT and the longrange propagation of waves in quantum mechanics or acoustics.…”
Section: ͑8͒mentioning
confidence: 99%